Economy at Cardiologic Risk - Adhikari, Roshan Prasad (Journal of Advanced Academic Research, 2017)
Cardiovascular disease should be prevented or overcome early period in order for letting expectable role in welfare package and rich contribution within the unitary construct of socio-cultural system when structure and function are reciprocated to by the inherent activity of an individual member. This research work is mixed, exploratory, with description of primary and secondary data rather a qualitative. Interrelationships among cardiovascular system, social and cultural factors are assessed and measured with standard at personal, familial and social background as known that incapacitation out of heart attack onslaught on eligibly participating candidates can threaten conducive affinity cast on track of progress; the attained disability does not allow which. An accumulation of total 330 respondents of four areas include coronary artery disorder of illiterate, literate, well educated, adopt and intellectual denizens. Their collection of altogether 330 coronary heart patients in four areas had included both arrogant and studious type of people. Among the victims 30 were pilot and 300 subject people for post study. Their 78.3% were literate, 64.8% intentional about socio-cultural performances where 25% had involved and whose participation 58.3% locals ever requested since remembered the previous many contributions at 43.9% degree. Their performances on various societal fields and prospective benefit which the heart complication if onslaught would finish up to where human expertise were mainly useful and an again local demands of those have indicated probability of surrounding gains during inclusion but development lag should have taken place instead of. Present researcher has faith on an actual transformation into systemic modification where societal process can meet culmination point, more than mental and physical health must remain sound, social terms coped better, and culture cherished through a consistent mutuality.